PROSODIC FEATURES OF THE IMPLEMENTATION OF ENGLISH MONOLOGUE AND DIALOGUE - Lyssenko , Catherine (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article deals with a description of the peculiarities of the intonational design of the interogatives of the monologue and dialogue. For an effective emotional influx, you can put in all your individual strength. The intonation of the interrogative both adds to the emotional appeal and may also weaken the interogativeness of the statement. Besides, the article differenciates low and high tones, which correlates with differences in their discursive function. The lower contour of the interogative is often used for detailing information, for introducing new ideas, or for further developing of current topics. The rising contour is most often used for supplementary information. Special questions, as a rule, can use the lower tone. A rising tone of voice expresses friendliness, interest and appreciation to the addressee, whereas a falling tone - the indifference and finality. The author also considers such a specific component of prosody as colloquiality. __________ References: • Vygotskij, L. S. Myshlenie i rech’, 5-e izd., ispr. (Moskva: Labirint, 1999), 352. • Jakubinskij, L. P. «O dialogicheskoj rechi.» Izbrannye raboty. Jazyk i ego funkcionirovanie (Moskva: Nauka, 1986), 208. • Gal’perin, I. R. Informativnost’ edinic jazyka (Moskva, 1974), 123. • Leont’ev, A. Psiholingvisticheskie edinicy i porozhdenie rechevogo vyskazyvanija (Moskva: Nauka, 1969), 307. • Borodina, S. «Fonostylistychni osoblyvosti anglijs’kogo movlennja dats’ko-anglijs’kyh bilingviv (na prykladi students’kogo sociolekta).» Avtoref. dys. kand. filol. nauk, Donec’k, 2008. • Koval’chuk, S. S. «Monolog kak rechevaja edinica dramaturgicheskogo teksta: na materiale rjada proizvedenij V. Shekspira.» (Diss. kand. filol. nauk, Moskva, 2007), 155. • Leshhyshyn, Z. Y. «Vnutrishnij dialog jak forma literaturnogo vykladu.» dys. kand. filol.nauk, L’viv, 2009. • Bahtin, M. M. Voprosy literatury i jestetiki (Moskva: Hudozhestvennaja literatura, 1976), 506. • Lotman, Ju. M. «Struktura hudozhestvennogo teksta.» Ob iskusstve (Sankt-Peterburg: Iskusstvo – SPB, 1998): 14–285. • Salova, N. Ju. «Monolog kak komponent hudozhestvennoj struktury jepicheskogo i dramaticheskogo tekstov: na materiale hudozhestvennyh proizvedenij M. Frisha i F. Djurenmatta.» dis. kand. filol. nauk, Sankt-Peterburg, 1999. • Velikaja, E. V. Prosodija v stilevoj differenciacii jazyka (Moskva: «Prometej» MPGU, 2009), 256. • Bloh, M. Ja., Velikaja, E. V. «Prosodija v stilizacii.» Monografija (Moskva: Prometej, 2012), 120. • Loseva, L. M. «Tekst kak edinoe celoe vysshego porjadka i ego sostavljajushhie.» Russkij jazyk v shkole 1 (1973): 61–102.285 • Strizhenko, A. A. «Vzaimodejstvie avtorskoj rechi i rechi personazhej v sovremennoj dramaturgii.» (Dis. kand. filol. nauk, Moskva, 1972), 178. • Krylova, O. A. Kommunikativnyj sintaksis russkogo jazyka (Moskva: Izd-vo Ros. un-ta druzhby narodov, 1992): 44. • Maslov, B. A. Problemy lingvisticheskogo analiza svjaznogo teksta (Moskva, 1968): 71. • Ershov, P. M. Tehnologija akterskogo iskusstva (Moskva: VTO, 1959): 120. • Petrova, A. N. Scenicheskaja rech’ (Moska, 1981): 86. • Anusas, P. P. «Foneticheskie harakteristiki odnostoronnej i mnogostoronnej rechi (jeksperimental’no-foneticheskoe issledovanie na materiale sovremennogo anglijskogo jazyka).» dis. kand. filol. nauk, Minsk, 1979. • Blohina, L. N., Potapova, R. K. Metodicheskie rekomendacii. Metodika analiza prosodii harakteristik rechi (Moskva, 1977), 56. • Nosenko, Je. L. Jemocional’noe sostojanie i rech’ (Kiev: Vishha shkola, 1981), 195. • Gaibova, M. T. Pragmalingvisticheskij analiz hudozhestvennogo teksta (Baku, 1986), 88. • Kovtunova,I. Pojeticheskij sintaksis (Moskva, 1986): 136. • Izotova, A. A. «Ob odnom sredstve jemocional’nogo vozdejstvija na chitatelja.» Jazyk, soznanie, kommunikacija (2006): 88–92. • Gnatishina, I. I. «Vnutrennjaja struktura monologa (na materiale proizvedenij U. Shekspira).» dis. kand. filol. nauk, Sankt-Peterburg. 2009. • Bloh, M. Ja., Velikaja, E. V. «Prosodija v stilizacii.» Monografija (Moskva: Prometej, 2012), 120. • Muhanov, I. L. «O tekstoobrazujushhej funkcii implicitnyh smyslov vyskazyvanija.» Implicitnost’ v jazyke i rechi (Moskva: Jazyki russkoj kul’tury, 1999): 88–94. • Lejbnic, G. V. Sochinenija v chetyreh tomah, t. 2 (Moskva: Mysl’, 1983), 686.Brovchenko,O., Bagmut, A. Y., Borysjuk, I. V., Olijnyk, G. P. «Intonacijni osoblyvosti movlennja radio i telebachennja na materiali suspil’no-politychnogo tekstu.» Intonacijna vyraznist’ zvukovogo movlennja zasobiv masovoi’ komunikacii’ (1994): 22–37. • Jackson, M. D. P. «Marina Tarlinskaja. Shakespeare and the Versification of English Drama, 1561–1642.» Style 49(4) (2015): 555. • Jaques, F. «L’interrogation. Force illocutoire et intéraction verbale.» Langue française 52 (1981): 70–79. • Apostel, L. «De l’interrogation en tant qu’action.» Langue française 52 (1981): 23–43. • Meyer, M. «La conception problématologique du language.» Langue française 52 (1981): 80–99. • Hlepit’ko, A. S. «Voprositel’noe predlozhenie i ego funkcii v rechi: na materiale francuzskogo jazyka.» (Dis. kand. filol. nauk, Moskva, 2008), 183. • D’Imperio, M. and House, D. «Perception of questions and statements in Neapolitan Italian.» Fifth European Conference on Speech Communication and Technology – 1997. • Hedberg, Nancy, Juan, M. Sosa, Emrah Görgülü, Morgan Mameni. The Prosody and Meaning of Wh-Questions (American English Department of Linguistics, Simon Fraser University, Burnaby, BC, V5A 1S6 Canada 2015).